Value chains: Talk about shared experience - St Clair, Roderick (Technical Centre for Agricultural and Rural Cooperation, 2012)
The Eat Caribbean project uses radio, podcasts, blogs and social networks to provide information on agricultural value chains to farmers and related businesses in the region.